Strategi Peningkatan Kualitas Barista dan Bartender di Hotel Four Points By Sheraton Bali Seminyak - Pramita, Ida Ayu Putu Mega; Parma, I Putu Gede (Universitas Pendidikan Ganesha, 2020)
This study aims to find out: (1) knowing what characteristics possessed by a professional barista and bartender, (2) knowing the obstacles faced by a barista and bartender at work, (3) knowing the efforts that must be made in improving barista and bartender skills . The method used in this research is descriptive qualitative. Data collection techniques used were observation and interviews. The subjects of this study were baristas and bartenders at the Four Points Hotel by Sheraton Bali Seminyak. Saddle, the object of this study is the characteristics of baristas and bartenders. The results showed that there are some requirements that must be possessed by a professional barista and bartender to improve the quality of service including having basic knowledge of coffee, having the ability to understand and master drinks, attitude or attitude and good communication. And there are some obstacles faced by baristas and bartenders in their work, which are different flavors of coffee, problematic espresso mechine, lack of preparation and guest complaints. Strategies used to improve the skills of a barista and bartender include training and participating in competitions related to baristas and bartenders.